PENINGKATAN KEMAMPUAN MENULIS PENGALAMAN MELALUI METODE PEMBERIAN TUGAS SISWA KELAS V SD NEGERI 001 PAGARAN TAPAH DARUSSALAM - Hasanah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low writing skills of fifth-grade students at SDN 001 Pagaran Tapah Darussalam. The purpose of this study was to improve students’ ability to write personal experiences through the assignment method, implemented over a period of one month. The subjects were 33 fifth-grade students at SDN 001 Pagaran Tapah Darussalam, consisting of 15 boys and 18 girls. The form of research used was classroom action research. The research instruments included teacher and student activity observation sheets and performance-based assessment tools. Based on the findings, it was revealed that the assignment method can improve the writing skills of fifth-grade students at SDN 001 Pagaran Tapah Darussalam. This is evident from: (a) an increase in teacher activity, which rose from 74.3% (Good) in the first cycle to 82.9% (Very Good) in the second cycle; and an increase in student activity, which rose from 71.1% (Good) in the first cycle to 75.8% (Good) in the second cycle; and (b) improved learning outcomes, shown by an increase in the average basic score from 64.4 to 70.9 in the first cycle, and further increasing to an average score of 85 in the second cycle.